Ø§Ù„ØªØºÙŠÙ†Ù‹: Ø§Ù„Ù†Ø¸Ø±Ø© Ø§Ù„Ø¹Ø§Ø¬Ù„Ø© Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„Ø¯Ø¹ÙˆØ© Ø§Ù„Ù…Ø³ØªÙ†Ø¨Ø·Ø© Ù…Ù† ØªÙØ³ÙŠØ± Ø§Ù„Ø£ÙŠØ© Ø§Ù„Ù‚Ø±Ø£Ù†ÙŠØ© - Mabrur, Muhammad (Alhadharah: Jurnal Ilmu Dakwah, 2012)
One of the characteristics of the message of Islam is 'taghyir' (change). It can be seen from the method of the Prophet preaching to jahiliyyah. Islamic Da'wah make changes in three characteristics. First, At-Taghyir Bil Kulli (total change). It is not limited to changes in the one aspect of human life, but it is a thorough manhaj. Therefore, Islam cannot be achieved by mere conjecture or 'irtijalli' (without the program). Second is At-Taghyir Bil Aqidah (changes with aqidah). Aqidah is the determinant of the nature of the change. It is necessary that every change should be guided by Shari'a. Third is Taghyir Bil Ihsan (change through humanity)